2009
DOI: 10.1007/s10238-009-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant phenotypes in childhood and adult acute leukemia and its association with adverse prognostic factors and clinical outcome

Abstract: Occurrence of aberrant phenotypes in childhood and adult acute leukemia (AL) differs considerably in independent studies and their association with prognostic factors is still controversial. In the present study, 214 patients with AL (106 children and 108 adults) were evaluated for the aberrant expression of CD33 in ALL (B cell and T cell) and CD3, CD5, CD7, and CD19 in AML. In B-ALL, aberrant expression of CD33 was found in 39 and 23% cases of adult and children, respectively. In T-ALL, CD33 was seen in 33% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
38
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 37 publications
21
38
4
Order By: Relevance
“…The frequency of aberrant myeloid antigen expression in the studied ALL group was 36.4%, our results are in accordance to 39% reported by Bhushan et al (2010), comparable to 21.2% (Paietta et al, 2001), and 55% reported by Wu et al (2007), while in contrast to others references (Pui et al, 1998;Vitaleet al, 2007).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leusupporting
confidence: 91%
See 2 more Smart Citations
“…The frequency of aberrant myeloid antigen expression in the studied ALL group was 36.4%, our results are in accordance to 39% reported by Bhushan et al (2010), comparable to 21.2% (Paietta et al, 2001), and 55% reported by Wu et al (2007), while in contrast to others references (Pui et al, 1998;Vitaleet al, 2007).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leusupporting
confidence: 91%
“…lymphoid antigen positive AML (Ly+AML) and myeloid Nahla Ahmad Bahgat Abdulateef 1,2 , Manar Mohammad Ismail 2,3 *, Hanadi Aljedani 1 antigen positive ALL (My+ALL) not classified as mixed phenotype leukemia (MPL). Aberrant antigen expression is reported to have variable frequency (Voskova et al, 2003;Vitale et al 2007;Zhang et al, 2012;Novoa et al, 2013) most commonly CD7 (Chang et al, 2007), CD9, CD19 and CD56 in AML cases (El-Sissy et al, 2006) as well as CD13 and CD33 in ALL (Liu et al, 2007;Suggs et al, 2007) and their prognostic and predictive relevance is controversial (Bhushan et al, 2010). However, several reports discussed their clinical significance, but most of them were not comprehensive (Putti et al, 1998;Venditti et al, 1998;Ogata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported in 10-47% of cases [23,26,27]. In our study, expression of CD13 and CD33 in B-ALL were 7.9 and 10.5%, respectively.…”
Section: Leukemia Subtypessupporting
confidence: 50%
“…An association was found between lymphocyte antigens positivity and expression of CD34 in our AML group as this aberrant expression was observed with highest percentage (93.8%) in AML-M0. Some published studies reported that lymphoid antigen positivity in AML between 16 and 22% and CD7 appeared to be the most commonly expressed marker [21][22][23].…”
Section: Leukemia Subtypesmentioning
confidence: 99%